The relationship between attribution of blame and the perception of resistance in relation to victims of sexual violence - de la Torre Laso, Jesús; Rodríguez-Díaz, Juan M. (Frontiers in Psychology, 2022)
Several studies have examined victim blaming in rape scenarios. However, there is limited research on the analysis of the perception of blame when two or more perpetrators are involved. The present article explores the perception of blame in cases involving rape based on the level of resistance shown by the victim and the presence of one or more perpetrators. A study was carried out involving 351 university students who responded to a survey after reading a hypothetical assault scenario. Six situations were established where the victim showed either low or high resistance, depending on whether the resistance was verbal or physical and verbal, and in the presence of one or two male perpetrators. It is expected that perpetrators are more culpable when acting in groups and that less resistance from the victim leads to greater attribution of blame. The results confirm that more blame is attributed to the perpetrators when they act in groups than when they act alone. Likewise, women consider the victim generally exerts greater resistance and this variable influences the attribution of greater blame.